Boomtown India creating greater divide between the rich and poor - Abd Razak, Dzulkifli (2007)
ONE cannot help but feel a tinge of envy on reading an article in the recent Forbes Asia (Nov 27) featuring India's richest. According to the article, the top 40 wealthiest have surged to more than double that of the previous year's— from US$170 billion (RM578 billion) to US$351 billion. This makes India's 40 by far the wealthiest of all in the AsiaPacific, it asserted. Among them, four are said to be worth an "astonishing US$180 billion", with 10 newcomers making the list this time.